Clinical hematology : theory and procedures. - Turgeon, Mary Louise, ....- (Philadelphia : Lippincott, Williams and Wilkins, 2005)
This established hematology text enters its Fourth Edition with even more of the focused coverage and learning tools that have made it so successful. Well illustrated and user-oriented, this new edition features extensive study and review tools, including learning objectives, case studies, procedure boxes, and review questions. Each chapter includes reader-friendly features: Chapters begin with a topical outline and behavioral objectives for a quick overview of content to be covered. Chapters conclude with highlights and new review questions to reinforce the student's understanding of key concepts and aid in test preparation. Summaries are highlighted for rapid reference and quick review. Features you'll find in this Fourth Edition include: Updated safety and phlebotomy information, and comprehensive coverage of automated instrumentation New information on peripheral stem cell and bone marrow transplantation, cytokines and gene therapy, sickle cell anemia, genetic and molecular aspects of acute leukemias, and malignant lymphoid and plasma cell dyscrasias A new expanded color insert increases coverage, allowing the user to view and differentiate hematologic disorders Additional case studies help with critical thinking Procedures are organized to adhere to the format suggested by the National Commission for Clinical Laboratory Standards (NCCLS)
Keywords: Hematologie